Developing a craft perspective on the interpretation and reconstruction of boats - Leijonhufvud, Fredrik (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In this article, analogue and digital methods for the surveying and reconstruction of boats are discussed from a boat builder’s perspective. The examples are from an ongoing study of vernacular clinker-built boats from the Stockholm Archipelago. The craft knowledge of the contemporary boat builder can be useful in the interpretation of old boats, and their reconstruction in practice, combined with cooperation between boat builders and marine archaeologists, may lead to synergetic results that improve related research.